Irrigation canal improvements in northern Utah for enhancing water resources management - Merkley, Gary P., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 2010)
A variety of improvements were made to the irrigation canals in two northern Utah counties during the past several years using state funding meant for enhancements in managing water resources. The improvements included operation and maintenance surveys and recommendations, calibrations of existing flow measurement structures, design and construction of flow measurement structures, measurement of seepage losses, and installation of water level recorders, data loggers, and telemetry systems for improved monitoring of flows. All of the work involved the participation of canal company management, and it was done at the request of the water users and or river commissioner, always in collaboration with state and local government agencies. Some of the results of this work include new flow measurement structures and recording/transmitting equipment, updated measurement structure calibrations, O&M recommendations, detailed GIS-based maps and photographs of the canals and structures, and maps and analysis of seepage losses in several canal reaches.
USCID water management conference
Presented at Upgrading technology and infrastructure in a finance-challenged economy: a USCID water management conference held on March 23-26, 2010 in Sacramento, California.